Consumption: hegemonic socio-communicative form of identification within the framework of capitalism as religion - Boito, María Eugenia (2016)
These reflections are oriented to define features and dynamics associated with consumption as hegemonic form of identification, which challenges the subjects in a transclass way. First, we start with the benjaminianas considerations that characterize capitalism as religion. Then we identify the performance of it upon the sensitivity, exposing forms of impoverishment of experience, associated with the phantasmagoria of the commodity and the forms/forces of daydream/ death, typical of capitalist drive. Finally we identify moments of practices which invert and/or cut through the materiality of scene of idolatry in the aforementioned consumption experience; interstices in which the demonic circulation / adaptation / restraint of men to things slows.